CALGARY FAMILY ASSESSMENT MODEL: WOMEN IN SITUATIONS OF VIOLENCE AND REVOCATION OF PROTECTIVE MEASURES - Rodrigues, Paula Sales; Alonso, Julia Santiago Cruz; Souza, Aline Pereira de; Sponchiado, Viviane Boacnin Yoneda; Vernasque, Juliana Ribeiro da Silva; Marin, Maria José Sanches (Cogitare Enfermagem, 2024)
Objective: To understand the strengths and weaknesses of the families of women in situations of violence who have had their emergency protective measures revoked. Method: descriptive research based on the Calgary Family Assessment Model, in the context of a Women's Police Station in a municipality in the interior of São Paulo, Brazil, carried out between September and November 2021, with four families of women who revoked the protective measure. Family structure, development, and functionality data were collected and analyzed according to the Calgary Model. Results: the families have similarities that include socio-economic aspects, low schooling, alcohol use, conflicting family relationships, and transgenerational relationships that, due to their fragility, perpetuate the cycle of violence. However, the social benefits, religious support, and family members were strengths. Conclusion: The Calgary Family Assessment Model guides nurses in proposing care plans consistent with domestic violence's complexities.